2021
DOI: 10.1007/jhep03(2021)264
|View full text |Cite
|
Sign up to set email alerts
|

Bulk interactions and boundary dual of higher-spin-charged particles

Abstract: We consider higher-spin gravity in (Euclidean) AdS4, dual to a free vector model on the 3d boundary. In the bulk theory, we study the linearized version of the Didenko-Vasiliev black hole solution: a particle that couples to the gauge fields of all spins through a BPS-like pattern of charges. We study the interaction between two such particles at leading order. The sum over spins cancels the UV divergences that occur when the two particles are brought close together, for (almost) any value of the relative velo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 48 publications
1
24
0
Order By: Relevance
“…While it seems not unlikely that the form of some of the obtained exact solutions should be reconsidered in view of the locality issue, some interesting information on their properties JHEP08(2021)144 can still be gained at free level. Particularly, a remarkable boundary interpretation of the linearized version of HS extremal black hole as a bi-local operator on the boundary was established in [61]. The same authors have also observed that a BPS-like pattern of the solution results in certain UV-cancellations of two interacting such black hole states at leading order.…”
Section: Jhep08(2021)144mentioning
confidence: 89%
“…While it seems not unlikely that the form of some of the obtained exact solutions should be reconsidered in view of the locality issue, some interesting information on their properties JHEP08(2021)144 can still be gained at free level. Particularly, a remarkable boundary interpretation of the linearized version of HS extremal black hole as a bi-local operator on the boundary was established in [61]. The same authors have also observed that a BPS-like pattern of the solution results in certain UV-cancellations of two interacting such black hole states at leading order.…”
Section: Jhep08(2021)144mentioning
confidence: 89%
“…While it seems not unlikely that the form of some of the obtained exact solutions should be reconsidered in view of the locality issue, some interesting information on their properties can still be gained at free level. Particularly, a remarkable boundary interpretation of the linearized version of HS extremal black hole as a bi-local operator on the boundary was established in [60]. The same authors have also observed that a BPS-like pattern of the solution results in certain UV-cancellations of two interacting such black hole states at leading order.…”
Section: Introductionmentioning
confidence: 89%
“…It is then natural to expect that the bilocal should play a key role in the bulk interactions dual to these boundary correlators. Now, the bulk dual of boundary bilocals was computed in [32], and identified in [33] as the linearized version [34] of the Didenko-Vasiliev solution, with the precise BPS-like pattern of HS charges dictated by the master-field description in [25]. We thus view the Didenko-Vasiliev solution as key to illuminating the structure of HS gravity, including its relationship with locality.…”
Section: Why Study the Didenko-vasiliev Solutionmentioning
confidence: 99%